2015
DOI: 10.1007/s10803-015-2414-9
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Preliminary Proposal of a Conceptual Model of a Digital Environment for Developing Mathematical Reasoning in Students with Autism Spectrum Disorders

Abstract: There is clear evidence that in typically developing children reasoning and sense-making are essential in all mathematical learning and understanding processes. In children with autism spectrum disorders (ASD), however, these become much more significant, considering their importance to successful independent living. This paper presents a preliminary proposal of a digital environment, specifically targeted to promote the development of mathematical reasoning in students with ASD. Given the diversity of ASD, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The data in this present study and that of Bouck et al (2014), Bassette, Bouck, Shurr, Park, and Creamans (2019), and Bassette, Bouck, Shurr, Park, Creamans, Rork, et al (2019) suggest that while both VM and CM can be a highly beneficial teaching tools for basic mathematic operations, VM may have a slight edge for young students with ASD. Students with ASD often have difficulties in mathematics related to deductive reasoning, problem solving, and abstract thinking (Santos et al, 2015). While CM can be part of a healthy mathematics instructional tool kit, VM can help students build conceptual understanding of basic computation and word-problem solving as they are able to visualize and interact with mathematical concepts in a virtual format.…”
Section: Discussionmentioning
confidence: 99%
“…The data in this present study and that of Bouck et al (2014), Bassette, Bouck, Shurr, Park, and Creamans (2019), and Bassette, Bouck, Shurr, Park, Creamans, Rork, et al (2019) suggest that while both VM and CM can be a highly beneficial teaching tools for basic mathematic operations, VM may have a slight edge for young students with ASD. Students with ASD often have difficulties in mathematics related to deductive reasoning, problem solving, and abstract thinking (Santos et al, 2015). While CM can be part of a healthy mathematics instructional tool kit, VM can help students build conceptual understanding of basic computation and word-problem solving as they are able to visualize and interact with mathematical concepts in a virtual format.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent research designs utilized by previous studies to demonstrate the efficacy of various computer technologies in supporting ASD-inclusive education include case studies [25,26,37], experimental designs [8,10,12,16,20,38], systems developments and implementations [15,17,21,29,30,32,47,48], mixed study designs [19, 22-24, 27, 28, 33-36, 39-42, 49-51], observation [18] and quantitative research methodologies [7,52]. Furthermore, the research methodologies were limited by small sample sizes and were mainly conducted in the US [7,12,25,34,35,[38][39][40][41][42][50][51][52], and European countries [10,15,17,26,27,32,37]. Noteworthy, many relevant studies utilized small sample sizes, lacking long-term data and evidence of consensus with best ASDinclusive practices.…”
Section: Analysis Of the Commonly Used Research Methodologiesmentioning
confidence: 99%
“…The systematic literature search of the present study identified the most frequently employed emerging computer technologies for ASD-inclusive education, as shown with the help of Figure 9 and Table 1. Several studies aimed at supporting learners with ASD in inclusive settings using various technologies including mobile applications [7,10,12,[27][28][29][30], educational robots [8,[21][22][23][24]49], gamified applications [25,26,48,52], video modeling [37][38][39][40], augmented reality [18][19][20], virtual reality [15][16][17], educational multimedia [34][35][36], maker program [50,51], wearable devices [41,42], and web applications [32,33]. Future studies must revisit the efficacy of the existing technological interventions and propose practical enhancements to provide sustainable strategies for ASDinclusive education in evolving societies.…”
Section: Analysis Of the Frequently Used Technological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEMA integrates modalities of dynamic adaptation of the activities proposed to the user. These activities are designed to promote the development of mathematical reasoning, having in account a preliminary study carried out with children aged between 6 and 12 years diagnosed with ASD [9]. The functional profiles of the selected students for this study have played, as naturally expected, a fundamental role in the design of these activities.…”
Section: Phases Of Empirical Workmentioning
confidence: 98%